2011
DOI: 10.1177/0960327111412802
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil peptides 1, 2 and 3 (HNP 1–3): elevated serum levels in colorectal cancer and novel marker of lymphatic and hepatic metastasis

Abstract: Preoperative high plasma HNP 1-3 levels are associated with colorectal cancer. The HNP 1-3 levels may procure information on patients with lymph node or hepatic metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…With this approach, we report in the present study, overexpression of ␣-defensins (HNP 1-3) in H-CC. HNP 1-3 are a group of peptides already identified in various other types of malignancies, including digestive, lung, and kidney cancers [29,[32][33][34][35]. HNP 1-3 are antimicrobial peptides mainly expressed in human neutrophils of the innate immune system but not in normal epithelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, we report in the present study, overexpression of ␣-defensins (HNP 1-3) in H-CC. HNP 1-3 are a group of peptides already identified in various other types of malignancies, including digestive, lung, and kidney cancers [29,[32][33][34][35]. HNP 1-3 are antimicrobial peptides mainly expressed in human neutrophils of the innate immune system but not in normal epithelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic approach was used to identify differentially expressed proteins between CRC and normal colon mucosa in our study and we successfully identified 802 proteins, including 68 of them were defined as differentially expressed proteins. Some of these differentially expressed proteins played important roles in CRC genesis, developing and progressing, such as GRP78, neutrophil defensin 3, plectin, and tropomyosin beta chain (14)(15)(16)(17). In order to reveal biological functions of these differentially expressed proteins, we used some integral bioinformation tools.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found discrepancies in HNP levels in sera [ 39 41 ], plasma [ 42 ] or biological fluids [ 41 ] of normal and various diseases including infectious diseases [ 41 , 43 , 44 ], metabolic diseases (e.g., diabetes) [ 45 , 46 ], cardiovascular disease [ 2 , 47 ], cancers of urinary bladder [ 42 ], colorectal cancer [ 40 ], colorectal adenoma [ 48 ] and colon carcinoma [ 39 ]. It has been reported that normal plasma levels of HNPs range from undetectable to 50–100 ng/ml.…”
Section: Discussionmentioning
confidence: 99%